Occupational diseases in Poland, 2014 - Neonila Szeszenia-Dąbrowska; Urszula Wilczyńska (Nofer Institute of Occupational Medicine, 2016)
Background: The aim of the annual analysis of the incidence of occupational diseases in Poland is to evaluate the extent of the incidence and to identify its causes as well as activities involving factors that are harmful or annoying to such an extent that they result in occupational diseases. Material and Methods: Occupational diseases reporting forms supplied to the Central Register of Occupational Diseases were used as the study material. Results: In 2014, there were 2351 cases of occupational diseases recorded, i.e., 16.5 cases per 100 thousand of employees. The most numerous categories comprised infectious or parasitic diseases (borreliosis), pneumoconiosis, voice disorders and hearing loss (in total 79.7% of cases). The main causative factors of occupational diseases were as follows: industrial dust containing free silica, tick-transmitted Borrelia spirochete, and the way the work is done, including excessive vocal effort, and noise. The highest incidence per 100 thousand workers were recorded in mining and quarrying (296), manufacturing (24.9), education (24.6), agriculture and forestry (24.2) sectors. Conclusions: Compared with the previous year, there was a slight increase in the number of cases of certified occupational diseases (6.2%), primarily due to the increased incidence of Lyme disease. The incidence of voice disorders among teachers continues to vary considerably in individual provinces (0-11.3/10 000), reflecting the use of non-uniform diagnostic and certification methods. Med Pr 2016;67(3):327-335